2018
DOI: 10.1016/j.patcog.2018.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Characterising shape patterns using features derived from best-fitting ellipsoids

Abstract: A method is developed to characterise highly irregular shape patterns, especially those appearing in biomedical settings. A collection of best-fitting ellipsoids is found using principal component analysis, and features are defined based on these ellipsoids in four different ways. The method is defined in a general setting, but is illustrated using two-dimensional images of dimorphic yeast exhibiting pseudohyphal growth, three-dimensional images of cancellous bone and three-dimensional images of marbling in be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Previous work demonstrated that the structure attributes used here were successful in automatically classifying trabecular bone into Sham, OVX, and OVX + Zol groups (Gontar et al. 2018 ; Asiri et al. 2020 ) and so seem to capture key variation in structure between the groups.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Previous work demonstrated that the structure attributes used here were successful in automatically classifying trabecular bone into Sham, OVX, and OVX + Zol groups (Gontar et al. 2018 ; Asiri et al. 2020 ) and so seem to capture key variation in structure between the groups.…”
Section: Discussionmentioning
confidence: 93%
“…These include fitting ellipsoids to local structure (Gontar et al. 2018 ; Doube 2015 ) and directly measuring local branching characteristics (Asiri et al. 2020 ).…”
Section: Model Details and Implementationmentioning
confidence: 99%
See 1 more Smart Citation